Low-Density Lipoprotein Receptor-Related Protein-1 Signaling in Angiogenesis - Mao, Hua; Xie, Liang; Pi, Xinchun (Frontiers in Cardiovascular Medicine, 2017)
Low-density lipoprotein (LDL) receptor-related protein-1 (LRP1) plays multifunctional roles in lipid homeostasis, signaling transduction and endocytosis. It has been recognized as an endocytic receptor for many ligands and is involved in the signaling pathways of many growth factor or cytokines. Dysregulation of LRP1-dependent signaling events contributes to the development of pathophysiologic processes such as Alzheimer’s disease, atherosclerosis, inflammation and coagulation. Interestingly, recent studies have linked LRP1 with endothelial function and angiogenesis, which has been under-appreciated for a long time. During zebrafish embryonic development, LRP1 is required for the formation of vascular network, especially for the venous development. LRP1 depletion in the mouse embryo proper leads to angiogenic defects and disruption of endothelial integrity. Moreover, in a mouse oxygen-induced retinopathy model, specific depletion of LRP1 in endothelial cells results in abnormal development of neovessels. These loss-of-function studies suggest that LRP1 plays a pivotal role in angiogenesis. The review addresses the recent advances in the roles of LRP1-dependent signaling during angiogenesis.